Interaction analysis of bucket bottom knife with soil to build up subbase - V. A. Nikolaev (Вестник СибАДИ)
Introduction. To solve the problem of accelerating the construction of roads, improving their quality, it is advisable to use a continuous action unit to form a underlying layer. The main working elements of this unit are buckets, which cut off the soil layer from below and side. At the same time, the bottom knife cuts off the ground layer from below, the right knife - on the side, and the console knife partially cuts the top layer of soil from below for the next bucket. In particular, the analysis of interaction with the ground of the bottom knife of the continuous action unit is of theoretical and practical interest. To do this, the lower knife is divided into elements and the interaction of these elements with the soil is analyzed. The consistent impact on the soil of many bottom knives, within the width of the grip of the unit, is replaced by the impact on the ground of one conventional bottom knife at a distance necessary for the development of one cubic meter of soil. The forces of interaction of the conventional bottom knife with the soil are called conditional forces.The method of research. The method of calculating energy costs when introducing the bottom knife into the ground is presented. In general, when introducing the bottom knife in the ground, there are energy costs: to separate the soil, to overcome the friction of the ground on the edge of the blade, to overcome the pressure of the ground on the face, to the rise of the ground, to the vertical acceleration of the ground by the phase, to overcome the friction of the ground on the face, to overcome the friction of the ground on the surface, to overcome the friction of the ground on the lower plane. The total energy costs of interacting with a one cubic metre soil are derived from the addition of private energy costs. The method of calculating the horizontal longitudinal force needed to move the bottom knife is given.Results. On the basis of the developed method, energy costs are calculated in the introduction of the lower knife: on the separation of the soil, on overcoming the friction of the ground on the edge of the blade, on overcoming the pressure of the ground on the face, on the rise of the ground, on the vertical acceleration of the ground face, on overcoming the friction of the ground on the fascia, to overcome the friction of the ground on the lower plane. Energy costs to overcome the friction of the ground on the surface of the bottom knife are zero, as the soil flies over it. The total energy costs of the bottom knife interact with the soil of one cubic meter. The horizontal long-lived force needed to move the bottom knife has been determined.Conclusion. As a result of the calculations: the energy needed to cut the ground with the bottom knives, about 5 kJ/cube m., horizontal longitudinal force needed to move the lower knife - 16 N. To determine the total energy costs of moving the boiler unit to remove the top layer of soil from the underlying layer of the road, you need to analyze the interaction with the soil of other elements of the bucket.